Carboxymethyl sago pulp/chitosan hydrogel as an immobilization medium for activated sludge for p-nitrophenol biodegradation - Ng, Si Ling; Yong, Kevin Jenn Ling; Pushpamalar, Janarthanan; Suat, Peng Sam (Wiley, 2019)
In this study, carboxymethyl sago pulp (CMSP) derived from sago waste was successfully crosslinked with ferric ions in the presence of chitosan forming a novel immobilization matrix for p-nitrophenol (PNP)-acclimated activated sludge. On the basis of the shortest biodegradation time of PNP, the optimized operational conditions of immobilization were found to be: 7 w/v% CMSP, 9 g L−1 of activated sludge, 0.1 M ferric ion, and 15 min of crosslinking time. Observable inhibited PNP biodegradation was exhibited by the suspended activated sludge at the initial PNP concentration of 400 mg L−1. In contrast, complete mineralization was achieved by the CMSP/chitosan-immobilized activated sludge (CMSP/Ch-AS) beads. The results revealed the important role of CMSP/Ch hydrogel in protecting activated sludge from the toxicity of PNP. The CMSP/Ch-AS beads could be reused consecutively up to three and two cycles, respectively, for the biodegradation of PNP at 200 and 400 mg L−1, with the attainment of more than 99% of PNP removal at each cycle